2010
DOI: 10.1007/s11433-010-0194-y
|View full text |Cite
|
Sign up to set email alerts
|

A study on the sharp knee and fine structures of cosmic ray spectra

Abstract: The paper investigates the overall and detailed features of cosmic ray (CR) spectra in the knee region using the scenario of nuclei-photon interactions around the acceleration sources. Young supernova remnants can be the physical realities of such kind of CR acceleration sites. The results show that the model can well explain the following problems simultaneously with one set of source parameters: the knee of CR spectra and the sharpness of the knee, the detailed irregular structures of CR spectra, the so-call… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Hu et al [25] proposed a model to simultaneously explain the knee and the e + e − excess, incorporating pair production interactions between CRs and the ambient photon field. It was further shown that the irregular structures of the CR spectra around the knee region and the galactic 'B component' could also be well explained in this scenario [31]. As a consequence, one set of parameters in the mode of [25] also favors the single-source model.…”
Section: Origin Of the Kneementioning
confidence: 89%
“…Hu et al [25] proposed a model to simultaneously explain the knee and the e + e − excess, incorporating pair production interactions between CRs and the ambient photon field. It was further shown that the irregular structures of the CR spectra around the knee region and the galactic 'B component' could also be well explained in this scenario [31]. As a consequence, one set of parameters in the mode of [25] also favors the single-source model.…”
Section: Origin Of the Kneementioning
confidence: 89%
“…However, the energy spectrum after the interactions is not simply a broken power law or a power law with cutoff. Due to the detailed interaction energy losses, there is both a pile-up effect and a high-energy tail of the particle spectrum (Hu et al 2009;Wang et al 2010). It is worth noting that the KASCADE experiment recently reported a discovery of ankle-like spectrum for light elements at about 10 PeV (Antoni et al 2005).…”
Section: Composition Models In the Kneementioning
confidence: 99%
“…As for the physically based interaction model, the flux of individual nuclei depends on the energy loss rate and can not be analytically parameterized. We adopt the numerical results presented in Wang et al (2010) in the calculation.…”
Section: Composition Models In the Kneementioning
confidence: 99%
“…Photodisintegration of the CR nuclei by interactions with optical and soft UV photons in the source region has also been considered (Karakula & Tkacsyk 2004;Candia et al 2002), but it does not succeed in describing the composition in the direct measurements realm and at the highest energies, as shown in Fig.26 (bottom right). A more recent proposal relates the knee to the e + e − pair production by CR nuclei interacting with background photons (Wang et al 2010). Finally, new hadronic interactions could take place in the atmosphere at very high energies.…”
Section: Models For the Kneementioning
confidence: 99%